The Effectiveness of The Stad-Type Cooperative Learning Model on The Mathematical Problem-Solving Ability of Elementary School Students - Yuliana Luthfi, Fajra; Murtiyasa, Budi (JTMT: Journal Tadris Matematika, 2024)
Students’ ability to solve problems is still lacking because they often rely on memorizing concepts. The purpose of this research is to determine the effectiveness of the STAD-type cooperative learning model in helping students solve mathematical problems. This type of research used descriptive quantitative research. This research approach used an experiment with a Quasi experimental design in the form of a pre-test post-test control group design. This research was conducted using a sample of fifth-grade students at Dukuhan Kerten State Elementary School, even semester of the 2022/2023 academic year. This research used a cluster random sampling technique where two experimental and control classes were obtained. Independent Sample T-Test is one type of data analysis test used. STAD and conventional learning models show different levels of effectiveness, as seen from the Sig. (2-tailed) of 0.044 < 0.05 indicated that is rejected. In the Independent sample t-test the mean value of the experimental class also bigger than the mean of the control class, which is 0.4280 > 0.2708. It showed that in improving fifth-grade students’class V mathematics problem solving skills on geometric material, the STAD learning model is more effective to use.